Exploring subtlety: collocational variation of the definite article in Inner and Outer Circle varieties of English - Abdul Wahid, Mohd Ridwan (2012)
Article usage variation is often said to manifest itself in terms of token omission and insertion e.g. American take me to the hospital vs. British take me to Ø hospital. Quantitative evidence, however, can only offer little support for the extensiveness of such variation (e.g. Sand, 2004). Given that syntactic variation in different varieties of English is rarely categorical in that one form exists in one variety but absent in another (e.g. Kortmann, 2006), this paper seeks to explore an aspect of the subtlety of article use variation by describing differences in collocational patterns of the in eight varieties of English available in the International Corpus of English: British, American, Australian, New Zealand, Indian, Singaporean, Philippine and Kenyan Englishes (Greenbaum and Nelson, 1996).